2004
DOI: 10.1097/01.ccm.0000108878.23703.e0
|View full text |Cite
|
Sign up to set email alerts
|

Does the storage time of transfused red blood cells influence regional or global indexes of tissue oxygenation in anemic critically ill patients?*

Abstract: Transfusion of stored leukodepleted red cells to euvolemic, anemic, critically ill patients has no clinically significant adverse effects on gastric tonometry or global indexes of tissue oxygenation. These findings do not support the use of fresh red cells in critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
145
2
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(160 citation statements)
references
References 28 publications
3
145
2
9
Order By: Relevance
“…The outcome of (some of) these studies are probably confounded by a lack of transfusion policy and the use of leukocyte-non-depleted RBC preparations. Our observations on lack of correlation between change in oxygenation, duration of MV or PICU stay and length of RBC storage are compatible with experimental and clinical data indicating no difference in regional or global indexes of tissue oxygenation, or patient outcome in critically ill adults with organ failure [4][5][6].…”
supporting
confidence: 72%
“…The outcome of (some of) these studies are probably confounded by a lack of transfusion policy and the use of leukocyte-non-depleted RBC preparations. Our observations on lack of correlation between change in oxygenation, duration of MV or PICU stay and length of RBC storage are compatible with experimental and clinical data indicating no difference in regional or global indexes of tissue oxygenation, or patient outcome in critically ill adults with organ failure [4][5][6].…”
supporting
confidence: 72%
“…Because of the importance of the original Marik and Sibbold study in the debate over the quality of stored red blood Patients receiving older blood had longer ICU stay but did not have a higher need for ICU care [51] Randomized trial of RBC < 10 or > 10 days in surgical and critically ill patients This largest well-conducted retrospective review found no association [53] Review of registry of all repeat midline sternotomy patients for CABG, valve, or both 321 Age of RBCs, associated in a regression model with in-hospital and out-of-hospital mortality Age of red blood cells, associated in a regression model with in-hospital and out-of-hospital mortality cells, Walsh and his colleagues at the Edinburgh Royal Infirmary reported a randomized, prospective double blind trial in 2004 [48]. Twelve patient volunteers in septic shock were randomized to receive transfusions with red blood cells stored for greater than 20 days, and 10 more were given red blood cells stored for less than 5 days.…”
Section: Data From Clinical Studiesmentioning
confidence: 99%
“…In a double-blind randomised trial, Walsh et al 9 evaluated changes in gastric perfusion and oxygenation in 22 mechanically ventilated, critically ill patients who required a RBC transfusion in the absence of haemorrhage. The authors were not able to detect any adverse effects of older leuco-reduced RBCs (all units stored for > 20 days) on gastric intramucosal pH or arterial-gastric mucosal carbon dioxide gap when compared with fresh RBC transfusions (all units stored for < 5 days) or with baseline pre-transfusion values.…”
Section: Randomised Controlled Trialsmentioning
confidence: 99%